Glaucomatous blindness in the Negev: a descriptive study of age, sex, and ethnic patterns. Issue 8 (August 1983) - David, R; Dan, Y; Stone, D H
Abstract : Two sources of data (a blind register and the records of a glaucoma clinic) were used to study the age, sex, and ethnic characteristics of sufferers of glaucomatous blindness in the Negev region of Israel. Glaucoma was found to be the cause of blindness relatively infrequently (10% of eyes) among the registered blind population. The rate of blindness from glaucoma in the population was 0.38/1000. Glaucomatous blindness affected more males than females and more individuals of Eastern and Western origin. A steep gradient of increasing number of blind with advancing age was found in both sexes and both ethnic groups, but the gradient was steeper in males and females of Eastern origin. These findings are consistent with the pattern expected of a developing country and represent the first descriptive profile of the pattern of personal characteristics of sufferers from glaucomatous blindness in this region. The ethnic pattern resembles what is known about the natural history of glaucoma in pigmented and nonpigmented races.